Biocidal Properties of Mixtures of Silver, Zinc and Copper Nanoparticles - Paliy, A.P.; Kolchyk, O.V.; Yaroshenko, M.O.; Sumakova, N.V.; Kovalenko, L.V.; Belikov, K.M.; Ganova, L.O.; Zavgorodnii, A.I.; Палій, А.П.; Колчик, О.В.; Ярошенко, М.О.; Сумакова, Н.В.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
Metal nanoparticles are becoming increasingly prevalent across a range of industrial sectors. Due to their physicochemical and antimicrobial properties, nanoparticles have gained popularity in the design of innovative antimicrobial compounds. The objective of this study was to investigate the bactericidal, fungicidal, and disinfectant properties of a mixture of metal nanoparticles, specifically Ag (151.2 mg/L), Zn (287.76 mg/L), and Cu (12.0 mg/L). Methods. In examining the biocidal properties of the nanocomposite, a variety of test cultures were utilized, including enterobacteria Escherichia coli No. 12, Staphylococcus aureus No. 5, microscopic fungi Aspergillus flavus, and helminth eggs Toxocara canis, which were obtained from the collection of pathogens of infectious animal diseases at the National Scientific Center "Institute of Experimental and Clinical Veterinary Medicine" (Kharkiv). The initial stage entailed the assessment of the bactericidal impact of the nanocomponent through the suspension method. Subsequently, the utilization of test objects was conducted. Results. The suspension method determined the antimicrobial properties of the Ag-Zn-Cu metal nanoparticle mixture. The most effective bactericidal effect on the test cultures of E. coli and S. aureus was observed in solutions with a concentration of nanoparticles of 22.5 mg/L and 45.1 mg/L, respectively, when the exposure time was between 1 and 5 hours. The complete disinfection of test objects contaminated with enterobacteria was achieved when the nanocomposite was applied at a concentration of 45.1 mg/mL for one hour. When determining the fungicidal (fungistatic) properties of the nanocomposite against the Aspergillus flavus suspension, it was found that the use of the agent in concentrations of 22.5–339.1 mg/L for 60–180 min caused a complete delay in the growth of the micromycete, while the nanocomposite in a concentration of 13.7 mg/L at an exposure time of 1 hour showed a fungistatic effect. The fungicidal properties of the nanocomposite against the test culture of the Aspergillus flavus species were observed at a concentration of 13.7 mg/L. Furthermore, at a concentration of 22.5 mg/L, a fungicidal effect was detected after one-hour exposure. It was determined that the nanocomposite, when administered at a concentration of 45.1 mg/L for 24 hours, was capable of disinfecting test objects contaminated with Toxocara canis eggs with an efficiency range of 88.3 to 94.2%. Conclusions. The nanocomposite, at a concentration of 22.5 mg/L by total metal content, exhibits bactericidal properties against Escherichia coli and Staphylococcus aureus, as well as fungicidal properties against Aspergillus flavus, when tested at an exposure time of 1 hour. At a concentration of 13.7 mg/L, the nanocomposite exhibits fungistatic properties against the test culture of a micromycete after exposure for 1 hour. Furthermore, the nanocomposite has a disinfection effect on Toxocara canis eggs at a concentration of 45.1 mg/L at an exposure time of 24 hours.